A new solution to the rational voter paradox - Mladenović Ivan; Vasić Miljan (Filozofija i Društvo)
The rational voter paradox suggests that there is no incentive for a rational individual to vote if the expected benefits are outweighed by the costs. However, the probability of an individual vote deciding the outcome of an election is typically small, making the expected benefits negligible. In response to the paradox, this paper proposes a novel solution based on Goldman’s causal responsibility approach, which asserts that voters make a partial causal contribution to the electoral outcome even if their vote is not decisive. The paper integrates the logic of Condorcet’s jury theorem into the causal responsibility approach, arguing that this leads to solving the rational voter paradox.